From humanism to Hobbes : studies in rhetoric and politics - Skinner, Quentin (Cambridge University, 2018)
The aim of this collection is to illustrate the pervasive influence of humanist rhetoric on early-modern literature and philosophy. The first half of the book focuses on the classical rules of judicial rhetoric. One chapter considers the place of these rules in Shakespeare's The Merchant of Venice, while two others concentrate on the technique of rhetorical redescription, pointing to its use in Machiavelli's The Prince as well as in several of Shakespeare's plays, notably Coriolanus. The second half of the book examines the humanist background to the philosophy of Thomas Hobbes. A major new essay discusses his typically humanist preoccupation with the visual presentation of his political ideas, while other chapters explore the rhetorical sources of his theory of persons and personation, thereby offering new insights into his views about citizenship, political representation, rights and obligations and the concept of the state.